2017
DOI: 10.1111/ijpo.12229
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of body fat and body mass index in young Pacific Islanders: a cross‐sectional study in European, Melanesian and Polynesian groups

Abstract: This study shows that Melanesian adolescents have lower %BF than their European counterparts for the same BMI z score. Therefore, the diagnostic accuracy of BMI to detect overfatness is related to ethnicity. Whatever the BMI-based reference, sensitivity was higher in the Melanesian group, while specificity was higher in the European group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Previous studies use BFP as gold standard to estimate accuracy of obesity variables to measure obesity status [36][37][38]. So, in this study, BFP was set as referenced standard of defining obesity to evaluate the accuracy of BMI and WHR indexes to distinguish obesity status in Chinese military personnel and healthy controls.…”
Section: Measurement Of Physical Parameter Assessmentmentioning
confidence: 99%
“…Previous studies use BFP as gold standard to estimate accuracy of obesity variables to measure obesity status [36][37][38]. So, in this study, BFP was set as referenced standard of defining obesity to evaluate the accuracy of BMI and WHR indexes to distinguish obesity status in Chinese military personnel and healthy controls.…”
Section: Measurement Of Physical Parameter Assessmentmentioning
confidence: 99%
“…These combined lifestyle variables are the root cause (but not unique) of noncommunicable diseases, and the young Pacific population is extremely exposed. The prevalence of overweight and obesity is very high in New Caledonian adolescents (from 36% to 43%, depending on age and the reference used to assess overweight) [ 9 , 10 , 11 ], and this is particularly the case for Melanesians. Indeed, a recent study showed that the prevalence of overweight/obesity was higher in 11 to 16-year-old Melanesian and Polynesian adolescents than in Caucasian adolescents, respectively, 38.2%, 30.4% and 21.3% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kessaram et al [10] reported the high prevalence of overweight and obesity in adolescents, likely explained by environmental mutations and shifts in nutrition and PA [12]. Traditional diets of root crops, vegetables, fruits and fresh fish and meat have been steadily replaced by imported, processed, energy-dense, low-nutrient foods [13], including SSBs. In six PICTs, 42% of 13- to 15-year-old students declared drinking SSBs daily [10].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas an “equitable school system” exists—i.e., offering every adolescent the same access to school and a standardized academic curriculum, as well as a health education program [17]—the differences between the ethnic communities may lead to dramatic consequences for health in future generations [18]. Although few studies have focused on 11- to 16-year-old adolescents in New Caledonia [13,19,20], the prevalence of overweight or obesity was found to be three times greater in New Caledonian adolescents than in French adolescents in the same age range [21]. In addition, Frayon et al [13] showed that in this multi-ethnic society, the risk of being overweight/obese was significantly greater in Polynesian and Melanesian adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation